Assessing Available Open-Source PACS Options. - Ghaderi, Hamidreza; April, Alain (Journal of Digital Imaging, 2023)
Medical imaging technology is producing a growing number of medical images types as well as patient-related information. The benefits of using modern medical imaging systems in healthcare are undeniable. Picture archiving and communication system (PACS) have revolutionized medical imaging practice. PACS have widely impacted the accessibility of medical images, reduced imaging costs, eliminated the physical storage of films, improved time management of radiologists, and allowed automated decision-making and diagnosis. Many health organizations and manufacturers have invested on developing commercial PACS. However, commercial PACS are not affordable for all hospitals while open-source PACS are increasingly becoming a viable option. Our research project is looking for an open-source PACS for the Donka University hospital of Guinea. Open-source PACS are currently available and are offering varying functionalities, documentation, and technical support from their developer communities. Selecting an open-source PACS is not an easy task and not only depends on the hospital requirements but also requires assessing each open-source PACS to find the best match. In this paper, the most popular open-source PACS are evaluated using a simple comparison approach based on four criteria. The result of this assessment shows that Orthanc, DCM4CHE, DCMTK, and Dicoogle are the most mature open-source PACS according to our criteria and the needs of Donka.